Airborne Particulates Around Frac Sand Plants Using Handheld Instruments - Fuhrman, Ethan; Burns, Joshua; Pierce, Crispin (My University, 2017)
Environmental exposure to airborne pollutants notably fine particulates (PM2.5) and crystalline silica (quartz) is of growing concern in western Wisconsin due to the expansion of industrial sand mining for hydraulic fracturing. Exposures to PM2.5 are associated with cardiovascular and lung disease while exposures to crystalline silica are associated with lung diseases such as silicosis, silico-tuberculosis, and lung cancer, as well as nonmalignant renal and autoimmune diseases. Under current regulatory structures in Wisconsin and many other states, direct air quality monitoring is rarely required (currently just 15% of facilities in WI). This research constitutes the continued use of laser-based, direct-reading instruments to measure fine particulates around industrial silica (frac) sand mining and processing facilities in Wisconsin. Consistent with results from other phases of this research, PM2.5 particulate levels were higher than regional DNR background levels. Data from these instruments are compared to EPA-certified filter-based air monitoring instruments as well as concurrent regional DNR PM2.5 concentrations.
Color poster with text, images, maps, and graphs.
Keywords: Airborne pollutants; Hydraulic fracturing; Posters